Hakikat Hukum Ekonomi (Internasional) Dalam Perspektif Teori Keadilan Bermartabat - Jeferson Kameo; Teguh Prasetyo (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The legal issue that is raised and examined in this article is the concern that has recently emerged behind the development of (international) economic law. As if the (international) economic law would threaten the sovereignty of countries. This type of research is normative legal research. The results of the research and discussion conclude that the anxiety over such (international) economic law developments is excessive. Even though it is necessary to make efforts as a sign of caution. It is proven that in (international) economic law does not override national law. The theory of dignified as a pure legal theory becomes a tool kit to describe at a glance the “face” of (international) economic law that should not be worried about. Each sovereign state must give consent before the rules and legal principles are applied and enforced within and among the countries that are binding themselves in a form of international agreement. It is at this stage of the approval that the filter with legal values in the soul of the nation (Volksgeist) that safeguards the sovereignty of a nation and state can be used to select (international) economic law.